The Effects of Tiered Tasks on Students’ Learning Achievement Across the Students’ Levels of Readiness - Yulianti, Delfita; Widya Syafitri (Language Pedagogy Study Program, Faculty of Languages and Arts, Universitas Negeri Padang, Indonesia, 2023)
Numerous studies have been conducted to investigate the effects of applying tiered assignments in the mixed-ability English as a foreign language classroom. Most of the studies were focused on students’ academic performance. There are still limited studies on the effects of tiered tasks on students’ learning achievement across the students’ levels of readiness since the implementation of tiered assignments in differentiated learning at Kurikulum Merdeka. So, this study was aimed at investigating the effects of using tiered tasks on students’ learning achievement across the students’ readiness levels in the Advanced English class pace F at SMAN 2 Lintau Buo. For the Advanced English class pace F, the tiered instructions were created to correspond with high, intermediate, and low levels of students’ prior knowledge. It involved one class as an experimental group and the other as a controlled group. The experimental class was given tiered tasks, and the other class used universal learning designs. The result of the study showed that there was a significant difference in scores between the students who received tiered tasks and those who did not receive tiered assignments. The high readiness students got has higher mean after they were taught by using tiered task. However, the same case cannot be said to the intermediate and low readiness students. Through this research, it became clear how important it is to have a strong understanding of the subject matter and to be aware of a variety of learning activities that can be adapted to the readiness levels of the students’ prior knowledge.